Analysis data of the 22 years of observations on the young crescent moon at Telok Kemang observatory in relation to the Imkanur Rukyah criteria 1995 - Nazhatulshima Ahmad,; Nur Izzatul Najihah Mohamad,; Raihana Abdul Wahab,; Mohd Saiful Anwar Mohd Nawawi,; Mohd Zambri Zainuddin,; Ibrahim Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The main challenge in the young crescent moon (YCM) observation is the ability to detect the appearance of the YCM, which has varying contrast due to the phenomenon of twilight. The advancement of technology in digital imaging helps the faint and thin image of the YCM to be detected and taken during observation. The techniques used in the observations of the YCM were naked eyes, telescope, and telescope with cameras. A digital imaging technique is also being used in the observations to assist in detecting and recording the image of the YCM more effectively. This paper presents the analysis of the YCM observation data recorded at Telok Kemang Observatory from 2000 to the present. A total of 275 observation sessions were conducted during this study, with 87 positive sightings successfully recorded. The studies found that the smallest elongation and the minimum altitude at sunset of the YCM successfully recorded were 6.81° and 5.40°, respectively. The moon was recorded at an altitude of 3.37°, while the sky is still bright with the sun at an altitude of –2.64° using the digital imaging technique. Based on the records, the YCM which has the minimum criteria of Imkanur Rukyah, i.e., altitude of 2° and elongation of 3° at sunset was never detected or recorded during the 22 years of observations. Therefore, this work suggests the need to change the visibility of Imkanur Rukyah criteria used since 1995 to a more potentially observable criterion. In other aspects, the lengthy observation activities have contributed to the development of a database system for JAKIM that other researchers can access.